2021
DOI: 10.1016/j.jdeveco.2020.102607
|View full text |Cite
|
Sign up to set email alerts
|

Female employment and intimate partner violence: Evidence from Syrian Refugee inflows to Turkey

Abstract: Any opinions expressed in this paper are those of the author(s) and not those of IZA. Research published in this series may include views on policy, but IZA takes no institutional policy positions. The IZA research network is committed to the IZA Guiding Principles of Research Integrity. The IZA Institute of Labor Economics is an independent economic research institute that conducts research in labor economics and offers evidence-based policy advice on labor market issues. Supported by the Deutsche Post Founda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 35 publications
(9 reference statements)
1
17
0
1
Order By: Relevance
“…A possible explanation of why these international businesswomen, who have a higher educational level, experience IPVAW, is because empowerment is not immediate protection against violence, as the male backlash theory predicts. As has been reported by various studies, female empowerment in terms of employment opportunities and higher educational achievement tend to increase domestic violence and abuse ( Heath, 2014 ; Erten and Keskin, 2018 , 2021 ; Bhalotra et al, 2021 ; Guarnieri and Rainer, 2021 ). Furthermore, even in a gender-equal country like Sweden, intimate partners tend to react with hostility and violence to an improved economic position of women ( Bergvall, 2022 ).…”
Section: Discussionmentioning
confidence: 71%
“…A possible explanation of why these international businesswomen, who have a higher educational level, experience IPVAW, is because empowerment is not immediate protection against violence, as the male backlash theory predicts. As has been reported by various studies, female empowerment in terms of employment opportunities and higher educational achievement tend to increase domestic violence and abuse ( Heath, 2014 ; Erten and Keskin, 2018 , 2021 ; Bhalotra et al, 2021 ; Guarnieri and Rainer, 2021 ). Furthermore, even in a gender-equal country like Sweden, intimate partners tend to react with hostility and violence to an improved economic position of women ( Bergvall, 2022 ).…”
Section: Discussionmentioning
confidence: 71%
“…Second, we examine the robustness of the results to the inclusion of unemployment rate as a control variable. While the direction of the link seem to the depend on the context, unemployment, which raised dramatically in Spain from year 2008, is a crucial determinant of IPV (see for example Anderberg et al 2016, Bhalotra et al 2021, Tur-Prats 2021or Erten and Keskin 2021.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Kizilgol and Ipek(2018) found that the employment status of women and men has no significant effect on any type of abuse in Turkey. Erten and Keskin(2020) investigated the effect of women's employment on violence by exploiting the Syrian refugee inflow in Turkey as an exogenous labor market shock. According to their findings, refugee inflows simultaneously reduced women's employment opportunities and reduction in IPV against women which is supporting the male backlash theory.…”
Section: Literature Reviewmentioning
confidence: 99%